Capturing the rapid response of sediments to low-oxygen conditions with high temporal resolution gas concentration measurements - Chua, Emily J.; Fulweiler, Robinson W. (Frontiers in Environmental Science, 2023)
Low-oxygen conditions plague coastlines worldwide. At present, little is known about how the transition from normoxic to low or even no oxygen conditions alters sediment biogeochemical cycling and ultimately ecosystem functioning. Conventional sediment core incubations cannot capture rapid (